Uprość wyrażenia
a) 5*(xy)

b) 3a przez 4 *(- 2a przez 3)

c) -2x*(-3xy)

d) x- x przez 2 - x przez 3

e) -4*(- x przez 2)*(-2x przez 4)

f) x+1 przez 2 + 2x-1 przez 4

g) -( x +1) + ( 2x +4)

h) 3(x do potengi 2 - 4) - ( -a do potengi 2 +2)

Pliska potrzebuje na jutro !!

3

Odpowiedzi

2009-09-20T21:44:07+02:00
A) 5*(xy)=5xy

b) 3a przez 4 *(- 2a przez 3)=12a*(-2a/3)=-6a

c) -2x*(-3xy)=6x²y

d) x- x przez 2 - x przez 3= 6x/6 - 3x/6 - 2x/6=

e) -4*(- x przez 2)*(-2x przez 4)=-x

f) x+1 przez 2 + 2x-1 przez 4=(4x+1)/4=x+1/4

g) -( x +1) + ( 2x +4)=-x-1+2x+4=x+3

h) 3(x do potengi 2 - 4) - ( -a do potengi 2 +2)=3x²-12+a²-2=3x²+a²-14
1 1 1
2009-09-20T21:50:55+02:00
A) 5*(xy)=5xy

12a•(-2a/3)=-6a

c) -2x•(-3xy)=6x²y

d) 6x/6 - 3x/6 - 2x/6=x/6

e) -4*(- x przez 2)•(-2x przez 4)=-x

f) x+1 przez 2 + 2x-1 przez 4=(4x+1)/4=x+1/4

g) -( x +1) + ( 2x +4)=-x-1+2x+4=x+3

h) 3(x do potengi 2 - 4) - ( -a do potengi 2 +2)=3x²-12+a²-2=3x²+a²-14
2009-09-20T21:51:20+02:00
A) 5*(xy)=5xy
b) 3a:4*(-2:3)=-½a²
c) -2x*(-3xy)=6x²y
d) x-x:2-x:3=x/6
e) -4*(-x:2)*(-2x:4)=-x²
f) x+1:2+2x-1:4=3x+¼
g) -(x+1)+(2x+4)=x+3
h) 3(x²-4)-(-a²+2)=3x²+a²-14

Mam nadzieję że dobrze ;)